Integrating Java Coding Into Project Based Learning In M-Learning Environment - Hasan, Syed Hamid; M. Alghazzawi, Daniyal; Zafar, Aasim (Malaysian Journal of Computer Science, 2017)
The widespread use of mobile phones among students supposes possibility to develop mobile learning tools. This paper discusses the design and development of a mobile courseware using project-based learning approach. The aim of designing the courseware is to study how feasible it is to adopt the learning pedagogies based on projects for mobile learning environments designed for technology and computing students. Java Programming is the basis of the case study, while the framework on which the courseware implements is M-Learning. PBL environment is used for depicting mobile learning’s learning objects delivery and design.